Three-dimensional relation of skin markers to lumbar vertebrae of healthy subjects in different postures measured by open MRI - Mörl, Falk (Springer-Verlag, 2005)
The debate is to which extent external skin markers represent true underlying vertebral position and motion. Skin markers and lumbar vertebrae L3 and L4 were examined by vertically open magnetic resonance imaging (MRI) within different postures to investigate whether, and to which extent the position and orientation of skin markers represent the corresponding information of assigned underlying vertebra. Nine healthy volunteers sat within an open MRI scanner in five different seating postures: upright, low flexion, heavy flexion, upright left turn and upright right turn. Skin markers were fixed at lumbar levels L3 and L4. A set of landmarks defines corresponding positions on the vertebrae. Translation-vectors quantify the change of co-ordinates while changing position. Orientation (Cardan-angles) of each level in space was calculated from co-ordinates of three skin-markers and the corresponding vertebral landmarks respectively. The close relation between the position of the individual skin marker and its corresponding landmark on the vertebrae is conserved through all postures (regression coefficients: 0.720<b<0.972, 0.916<r<0.993, p<0.0001). Despite the high sensitivity to measurement errors there is a strong relation between the translation-vectors of external markers and the corresponding translation of the landmark on the vertebrae (0.68<r<0.99, p<0.0001). Within the resolution of the MR-imaging the orientation of the vertebrae can be predicted from the external markers (regression coefficients: 0.936<b<1.189, 0.769<r<0.959, p<0.0001). Positions and motions of skin markers can be taken as a first estimate to calculate the position and spatial orientation of underlying vertebrae. The use of skin markers may help to investigate spinal positions in daily life situations where internal imaging is not possible.